Against the tide [large type] - Martin, Kat (Martin, Kat. Brodies of Alaska., 2015)
While running from a dangerous secret in her past, diner owner Liv Chandler gets drawn into investigating a murder in remote Valdez, Alaska with charter boat captain Rafe Brodie.